MBAS AND ENTREPRENEURSHIP: A PERFECT PAIRING OR POTENTIAL MISMATCH? - Kleinova, Ivona (DeReMa (Development Research of Management): Jurnal Manajemen, 2024)
The world economy has been experiencing and indeed appreciating the golden era of entrepreneurialism for quite some time now. The crucial element in this movement is entrepreneurs plentifully consuming accessible know-how and contemplating various funding options while benefiting from the digitised and globalised world. However, they often fail to succeed. In this paper, I assess the experience and knowledge of MBA graduate entrepreneurs on starting and running real businesses. I aim to explore what areas of new business development an MBA assists a nascent entrepreneur in launching a business. The research also intends to explore crucial MBA management tools and strategies vital in the start-up phase of a new business. To establish valid and robust empirical findings, I in-depth interviewed 10 MBA graduate entrepreneurs best acquainted with the research area. The study highlighted several areas within a new business formation where an MBA could assist a new entrepreneur and indicates as many as 26 MBA management tools and strategies that can be employed.Abstrak dalam Bahasa Indonesia. Ekonomi dunia telah mengalami dan benar-benar menghargai era keemasan kewirausahaan untuk waktu yang cukup lama. Elemen krusial dalam gerakan ini adalah para pengusaha yang melimpah mengonsumsi pengetahuan yang mudah diakses dan mempertimbangkan berbagai pilihan pendanaan sambil memanfaatkan dunia yang terdigitalisasi dan terglobalisasi. Namun, mereka seringkali gagal untuk berhasil. Dalam makalah ini, saya menilai pengalaman dan pengetahuan para pengusaha lulusan MBA dalam memulai dan menjalankan bisnis nyata. Saya bertujuan untuk menjelajahi bidang-bidang pengembangan bisnis baru di mana seorang MBA membantu seorang pengusaha pemula dalam meluncurkan bisnis. Penelitian ini juga bermaksud untuk menjelajahi alat-alat manajemen dan strategi MBA yang penting dalam fase awal sebuah bisnis baru. Untuk mendapatkan temuan empiris yang valid dan kuat, saya melakukan wawancara mendalam dengan 10 pengusaha lulusan MBA yang paling akrab dengan area penelitian. Studi ini menyoroti beberapa area dalam pembentukan bisnis baru di mana seorang MBA dapat membantu seorang pengusaha baru dan menunjukkan sebanyak 26 alat manajemen dan strategi MBA yang dapat digunakan.